Development of a Biodegradable Panel using Rice Straw and Saw Dust for an Acoustic and Thermal Properties - Saravanan, Divasheeny; Mohd Sari, Kamarul Aini; Mohamed Yusop, Fatimah (Progress in Engineering Application and Technology, 2022)
The expanding use of acoustic panels in industry, particularly for the acoustics of buildings, has increased demand for them. However, the synthetics used in most of the commercial acoustics product cannot be disposed of in nature as solid waste or burned in industry, moreover, have an effect on human health. Therefore, this study was conducted to develop a biodegradable panel using rice straw, saw dust and corn starch to obtain sound absorption and thermal conductivity properties. The samples are divided into three, with separate proportions 70%, 50%, 30% of rice straw and saw dust respectively, with corn starch as binder. The objectives of this study are to identify suitable proportion of rice straw, saw dust and corn starch for biodegradable panel, to measure physical, acoustic and thermal properties of the panel and to compare with previous acoustics panels and gypsum board. The mixture is then set in a mould and ready press with the hot press at 105 °C for 15 minutes with pressure 1.0 tonne. Three types of testing were tested physically, acoustical and thermal conductivity. Saw dust (70%) and rice straw (30%) showed the maximum sound absorption coefficients at low and high frequencies, respectively. It's 241.9 kg/m3 dense. Rice straw (70%) and sawdust (30%) have the highest heat conductivity. This sample is denser, at 255.56 kg/m3. Thermal conductivity, sound absorption, and density are interrelated. Sound absorption reduces density. Density raises thermal conductivity. Compared to gypsum board, acoustics panel has 0.07 low frequency sound absorption coefficient at 400 Hz. At 4000 Hz, gypsum board sound absorption is 0.11 and acoustics panel is 0.9. Gypsum board and acoustic panel are alike. Saw dust (70%) and rice straw (30%) can replace gypsum board.